Corporate Governance and Ubuntu: a South African and Namibian perspective - Harris, Aisha-Deva (Department of Commercial Law, 2022)
Over the past two decades the emphasis on corporate governance practice has increased globally. The corporate governance models which guide corporate ethics, currently employed in African countries, are extensively driven by Western elements. Corporate governance practice in relation to the African philosophy of Ubuntu is under analysed. While Ubuntu has been studied comprehensively in a number of legal disciplines, it has not enjoyed comparable attention in its application, relevance, and potential to enhance corporate governance practices in Africa. Limited academic research exists on the integration of the Ubuntu philosophy into corporate governance and the ethical perspectives introduced. Therefore, this dissertation aims to bridge this gap by exploring the current guiding frameworks of selected corporate governance practice in relation to the principle of the African philosophy of Ubuntu. Here, corporate governance practice is examined in South Africa and Namibia. Business ethics, ethical perspectives, corporate social responsibility, and the African notion of Ubuntu, in relation to the role that it plays in ethical leaderships, is evaluated. Links between Ubuntu and established Western ethical perspectives and theories support its use and significance for enhancing current corporate governance frameworks in these countries. The findings of this dissertation strengthen the need to analyse Ubuntu, particularly in relation to its link with social responsibility and ethical perspectives, in order to augment current corporate governance practices in Africa. It is submitted that corporate governance practices in Africa should reflect the notions of Ubuntu more clearly and coherently which will serve as a progressive model to enhance effective corporate governance.